Toxicity hazard of organophosphate insecticide malathion identified by in vitro methods - Jira, David; Janousek, Stanislav; Pikula, Jiri; Vitula, Frantisek; Kejlova, Kristina (Neuro endocrinology letters, 2012)
OBJECTIVES: Malathion is generally not classified as toxic. However, the toxicity seems to be species-dependent. Local and systemic toxicity data for birds are rare, but a decrease of wild bird densities in areas where malathion was applied was reported. Aim of the study was to extend knowledge on malathion toxicity on cellular and organ level and to evaluate embryotoxicity and genotoxicity for birds using the chick embryo model HET-CAM. METHODS: Skin and eye irritation was determined using reconstructed skin and eye cornea tissues and the chorioallantoic membrane of chick embryo to simulate conjunctiva. Cytotoxicity in 3T3 Balb/c fibroblast culture was determined to estimate acute systemic toxicity. Chick embryo model was further employed to evaluate acute embryotoxicity for birds (mortality and genotoxicity). Data were analysed by means of general linear models. RESULTS: Malathion is not a skin and eye irritant. Cytotoxicity in vitro test provided LD50 value of 616 mg/kg suggesting higher toxic potential than is generally published based on in vivo tests on laboratory rodents. Embryotoxicity studies revealed dose and age dependent mortality of chick embryos. Genotoxicity was identified by means of micronucleus test in erythroid cells isolated from chorioallantois vascular system of chick embryos. CONCLUSIONS: Using in vitro alternative toxicological methods, a higher toxic potential of malathion was demonstrated than is generally declared. An increased health and environmental hazard may occur in areas with intensive agricultural production. The environmental consequences of delayed effects and embryotoxicity for bird populations in areas exposed to organophosphate insecticides, such as malathion, are obvious.
Keywords: lineární modely; Dose-Response Relationship, Drug; vztah mezi dávkou a účinkem léčiva; BALB 3T3 Cells; chorioalantoická membrána; techniky in vitro; Chickens; testy akutní toxicity; Chorioallantoic Membrane; Mice; buňky BALB 3T3; insekticidy; Malathion; kur domácí; Toxicity Tests, Acute; Irritants; In Vitro Techniques; Linear Models; embryo nesavčí; mitóza; malathion; Embryo, Nonmammalian; Chick Embryo; biologické modely; rohovka; Cornea; myši; dráždivé látky; druhová specificita; Insecticides; zvířata; kuřecí embryo; Animals; Species Specificity; Models, Biological; Mitosis